Magnetic wedge and rotary electric machine
By using a magnetic wedge composed of multiple planar magnetic metal particles and dielectric materials, the existing magnetic wedge lacks magnetic and electrical properties, and the high efficiency and excellent thermal mechanical properties of the rotating motor are achieved.
Patent Information
- Application Number
- JP2023156244
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-21
- Publication Date
- 2025-04-03
- Estimated Expiration
- 2043-09-21
AI Technical Summary
The magnetic and electrical properties of existing magnetic wedges are insufficient, resulting in large harmonic losses of rotating motors, limited efficiency improvement range, and also lack of thermal stability and mechanical properties.
A magnetic wedge consisting of a plurality of planar magnetic metal particles and indirect phases, which at least 10% of the length in cross-section exceeds the contour average, combines a surface coating and a diphase material to improve magnetic, electrical and thermomechanical properties.
It improves the magnetic and electrical properties of the magnetic wedge, reduces harmonic losses of the rotating motor, improves efficiency, and performs excellently in thermal stability and mechanical properties.
Smart Images

Figure 2025047639000001_ABST
Abstract
Description
[Technical field]
[0001] An embodiment of the present invention relates to a magnetic wedge and a rotating electric machine. [Background technology]
[0002] Usually, the coil winding of a rotating electric machine is housed in an iron core slot and supported and fixed by a wedge provided at the slot opening. A non-magnetic material is generally used for the material of the wedge, but since the magnetic resistance value in the gap between the stator iron core and the rotor iron core becomes discontinuous, pulsation occurs in the magnetic flux distribution on the iron core surface facing the wedge through the gap, and harmonic loss increases. In order to reduce this harmonic loss, a wedge with moderate magnetic properties (magnetic wedge) has been provided for some time. By applying the magnetic wedge, harmonic loss is reduced and the efficiency of the rotating electric machine is improved. FIG. 1 is a schematic diagram of the use state of the magnetic wedge and the effect of the magnetic wedge. FIG. 1 shows a radial gap type rotating electric machine as an example. FIG. 1 shows a magnetic wedge 100, a coil 230, an iron core tooth 250, and an iron core slot 260.
[0003] It goes without saying that the higher the magnetic permeability of the magnetic wedge, the more the harmonic loss can be reduced. However, as shown in FIG. 1, the magnetic wedge is arranged so as to bridge the adjacent iron core teeth, and therefore there is a drawback in that the leakage magnetic flux flowing between the iron core teeth through the magnetic wedge increases. In addition, the existing magnetic wedge is prone to magnetic saturation due to its low saturation magnetization, and furthermore, has a large loss (high coercive force results in large hysteresis loss, and low electrical resistivity results in large eddy current loss), so the efficiency improvement range of the rotating electric machine is limited. In addition, the existing magnetic wedge has a low magnetic permeability, so the efficiency improvement range of the rotating electric machine is limited, and it is insufficient in terms of thermal stability and mechanical properties (strength, toughness). Therefore, it is desired to improve the properties of the magnetic wedge in terms of saturation magnetization, magnetic permeability, loss, strength, toughness, etc. In particular, it is desired to improve the magnetic properties, electrical properties, and thermomechanical properties. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Utility Model Application Publication No. 58-6572 Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present invention is to provide a magnetic wedge and a rotating electric machine having excellent magnetic and electrical characteristics. [Means for solving the problem]
[0006] The magnetic wedge of the embodiment is a magnetic wedge for a rotating electric machine, and the magnetic wedge comprises a plurality of flat magnetic metal particles and intervening phases, and in a cross section perpendicular to the longitudinal direction of the magnetic wedge and at the center of the longitudinal direction, the magnetic wedge includes flat magnetic metal surface particles that are positioned outside the average contour line in the width direction of the magnetic wedge, with more than 10% of their length being located outside the average contour line in the width direction of the magnetic wedge. [Brief description of the drawings]
[0007] [Figure 1] 1 is a schematic diagram showing the use of a magnetic wedge and the effect of the magnetic wedge. [Diagram 2] 4 is a conceptual diagram showing an example of a method for determining the thickness of a flat magnetic metal particle in the magnetic wedge of the first embodiment. FIG. [Diagram 3] 2 is a conceptual diagram for explaining how to determine the maximum length and minimum length within the flat surface of a flat magnetic metal particle in the magnetic wedge of the first embodiment. FIG. [Figure 4] A conceptual diagram for explaining another example of how to determine the maximum length and minimum length within the flat surface of a flat magnetic metal particle in the magnetic wedge of the first embodiment. [Diagram 5] 1 is a schematic diagram showing the direction in which the coercive force of a magnetic wedge according to a first embodiment was measured, changing direction every 22.5 degrees relative to an angle of 360 degrees within the flat surface of a flat magnetic metal particle. FIG. [Figure 6] 2 is a schematic diagram of a flat magnetic metal particle in the magnetic wedge of the first embodiment. FIG. [Figure 7]FIG. 2 is a schematic diagram of a magnetic wedge according to the first embodiment. [Figure 8] FIG. 2 is a schematic diagram of a magnetic wedge according to the first embodiment. [Figure 9] 4 is a cross-sectional photograph example of a magnetic wedge according to the first embodiment. [Figure 10] FIG. 2 is a schematic diagram of a magnetic wedge according to the first embodiment. [Figure 11] FIG. 6 is a schematic diagram showing an example of a radial gap type rotating electric machine according to a second embodiment. [Figure 12] FIG. 6 is a schematic diagram showing an example of an axial gap type rotating electric machine according to a second embodiment. [Figure 13] FIG. 6 is a schematic diagram showing an example of a generator according to a second embodiment. [Figure 14] FIG. 6 is a schematic diagram illustrating an example of a linear motor according to a second embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Hereinafter, the embodiments will be described with reference to the drawings. In the drawings, the same or similar parts are denoted by the same or similar reference numerals. In this specification, unless otherwise specified, measurements are performed at 25°C.
[0009] In this specification, the "axial direction," "rotational direction," and "radial direction" are defined based on the rotor of the rotating electric machine. That is, the "axial direction" refers to the direction along the rotational axis of the rotor, the "rotational direction" refers to the circumferential direction around the rotational axis of the rotor (or the tangential direction thereof), and the "radial direction" refers to the direction perpendicular to (perpendicular to) the rotational axis of the rotor.
[0010] (First embodiment) The magnetic wedge of the embodiment is a magnetic wedge for a rotating electric machine, and the magnetic wedge comprises a plurality of flat magnetic metal particles and intervening phases, and in a cross section perpendicular to the longitudinal direction of the magnetic wedge and at the center of the longitudinal direction, the magnetic wedge includes flat magnetic metal surface particles that are positioned outside the average contour line in the width direction of the magnetic wedge, with more than 10% of their length being located outside the average contour line in the width direction of the magnetic wedge.
[0011] The flat magnetic metal particles are flaky particles (flattened particles) having a flaky (flattened) shape (flaky shape, flattened shape).
[0012] The thickness means the average thickness of one flat magnetic metal particle. The method of determining the thickness is not limited as long as it can determine the average thickness of one flat magnetic metal particle. For example, a method may be used in which a cross section perpendicular to the flat surface of a flat magnetic metal particle is observed with a transmission electron microscope (TEM), a scanning electron microscope (SEM), an optical microscope, or the like, and 10 or more arbitrary points are selected in the direction of the flat surface in the observed cross section of the flat magnetic metal particle, the thickness at each selected point is measured, and the average value is adopted. Also, a method may be used in which 10 or more points are selected at equal intervals from one end to another end in the direction of the flat surface in the observed cross section of the flat magnetic metal particle (at this time, it is preferable not to select the end and the other end because they are special places), the thickness at each selected point is measured, and the average value is adopted. FIG. 2 is a conceptual diagram showing an example of a method of determining the thickness of a flat magnetic metal particle in the magnetic wedge of the first embodiment. FIG. 2 specifically shows how to determine the thickness in this case. Ten points are selected at equal intervals from one end to the other end in the direction of the flat surface (excluding the ends), and the thicknesses at each point are t1, t2, . . ., t 10 Then, the thickness of the flat magnetic metal particle is (t1+t2+...+t 10 ) / 10. It is preferable to measure as many points as possible, since this allows obtaining average information. If the cross-sectional contour line is very uneven or has a rough surface, making it difficult to determine the average thickness as is, it is preferable to smooth the contour line with an average straight line or curve, as appropriate, before carrying out the above method.
[0013] In addition, the average thickness refers to the average value of the thicknesses of a plurality of flat magnetic metal particles, and is distinguished from the above-mentioned simple "thickness". When determining the average thickness, it is preferable to adopt an average value for 20 or more flat magnetic metal particles. In addition, it is preferable to determine the average thickness for as many flat magnetic metal particles as possible, since average information can be obtained. In addition, if it is not possible to observe 20 or more flat magnetic metal particles, it is preferable to observe as many flat magnetic metal particles as possible and adopt an average value for them. The average thickness of the flat magnetic metal particles is preferably 10 nm or more and 100 μm or less. More preferably, it is 10 nm or more and 1 μm or less, and even more preferably, it is 10 nm or more and 100 nm or less. In addition, it is preferable that the flat magnetic metal particles include those having a thickness of 10 nm or more and 100 μm or less, more preferably, 10 nm or more and 1 μm or less, and even more preferably, it is 10 nm or more and 100 nm or less. These are preferable because they can sufficiently reduce eddy current loss when a magnetic field is applied in a direction parallel to the flat surface. In addition, a smaller thickness is preferable because the magnetic moment is confined in a direction parallel to the flat surface, and magnetization easily proceeds by rotational magnetization. When magnetization proceeds by rotational magnetization, the magnetization tends to proceed reversibly, so the coercive force is small, which is preferable because hysteresis loss can be reduced.
[0014] The average length of the flat magnetic metal particles is defined as (a+b) / 2, using the maximum length a and the minimum length b in the flat plane. The maximum length a and the minimum length b can be obtained as follows. For example, consider a rectangle with the smallest area among the rectangles circumscribing the flat plane. The length of the long side of the rectangle is the maximum length a, and the length of the short side is the minimum length b. FIG. 3 is a conceptual diagram for explaining how to obtain the maximum length and minimum length in the flat plane of the flat magnetic metal particles in the magnetic wedge of the first embodiment. FIG. 3 is a schematic diagram showing the maximum length a and the minimum length b obtained by the above method using several flat magnetic metal particles as examples. The maximum length a and the minimum length b can be obtained by observing the flat magnetic metal particles with a TEM, SEM, or optical microscope, as with the average thickness. It is also possible to obtain the maximum length a and the minimum length b by performing image analysis of the micrograph on a computer. In either case, it is preferable to obtain the maximum length a and the minimum length b from 20 or more flat magnetic metal particles. It is also preferable to obtain the maximum length a and the minimum length b from as many flat magnetic metal particles as possible, since average information can be obtained. In addition, when it is not possible to observe 20 or more flat magnetic metal particles, it is preferable to observe as many flat magnetic metal particles as possible and adopt the average value for them. In addition, since it is preferable to obtain an average value as much as possible, it is preferable to perform observation or image analysis in a state where the flat magnetic metal particles are uniformly dispersed (a state where multiple flat magnetic metal particles with different maximum and minimum lengths are dispersed as randomly as possible). For example, it is preferable to perform observation or image analysis by thoroughly mixing multiple flat magnetic metal particles and pasting them on a tape, or dropping multiple flat magnetic metal particles from above and pasting them on a tape.
[0015] However, depending on the flat magnetic metal particle, when the maximum length a and the minimum length b are obtained by the above method, the method may not capture the essence. FIG. 4 is a conceptual diagram for explaining another example of the method of obtaining the maximum length and the minimum length in the flat surface of the flat magnetic metal particle in the magnetic wedge of the first embodiment. For example, in the case of FIG. 4, the flat magnetic metal particle is in an elongated and curved state, but in this case, the maximum length and the minimum length of the flat magnetic metal particle are essentially the lengths a and b shown in FIG. 4. Thus, the method of obtaining the maximum lengths a and b is not completely unique, and basically, there is no problem with the method of "considering the rectangle with the smallest area among the rectangles circumscribing the flat surface, and setting the length of the long side of the rectangle as the maximum length a and the length of the short side as the minimum length b", but depending on the shape of the particle, if this method does not capture the essence, the maximum length a and the minimum length b that capture the essence are obtained flexibly. The thickness t is defined as the length perpendicular to the flat surface. The ratio A of the average length in the flat plane to the thickness is defined as A=((a+b) / 2) / t, where a is the maximum length, b is the minimum length, and t is the thickness.
[0016] The average ratio of the average length within the flat surface to the thickness of the flat magnetic metal particles is preferably 5 to 10,000. This is because it increases the magnetic permeability. In addition, it is because it is possible to increase the ferromagnetic resonance frequency and therefore reduce the ferromagnetic resonance loss.
[0017] The average value is used for the ratio of the average length in the flat surface to the thickness. It is preferable to use an average value for 20 or more flat magnetic metal particles. It is also preferable to obtain average information by targeting as many flat magnetic metal particles as possible. If it is not possible to observe 20 or more flat magnetic metal particles, it is preferable to observe as many flat magnetic metal particles as possible and use the average value for them. For example, when there are particles Pa, particles Pb, and particles Pc, and their respective thicknesses Ta, Tb, and Tc and their average lengths in the flat surface La, Lb, and Lc are given, the average thickness is calculated as (Ta+Tb+Tc) / 3, and the average value of the ratio of the average length in the flat surface to the thickness is calculated as (La / Ta+Lb / Tb+Lc / Tc) / 3.
[0018] It is preferable that the flat magnetic metal particles have a coercive force difference depending on the direction in the flat plane. The larger the ratio of the coercive force difference depending on the direction, the more preferable, and it is preferably 1% or more. More preferably, the ratio of the coercive force difference is 10% or more, even more preferably, the ratio of the coercive force difference is 50% or more, and even more preferably, the ratio of the coercive force difference is 100% or more. The ratio of the coercive force difference here is defined as (Hc(max)-Hc(min)) / Hc(min)×100(%), using the maximum coercive force Hc(max) and the minimum coercive force Hc(min) in the flat plane. The coercive force can be evaluated using a vibrating sample magnetometer (VSM) or the like. When the coercive force is low, a coercive force of 0.1 Oe or less can also be measured by using a low magnetic field unit. The measurement is performed by changing the direction in the flat plane with respect to the direction of the measurement magnetic field.
[0019] In addition, "having a coercive force difference" means that when a magnetic field is applied in the 360-degree direction in the flat plane and the coercive force is measured, there is a direction in which the coercive force is maximum and a direction in which the coercive force is minimum. For example, when the coercive force is measured by changing the direction every 22.5 degrees with respect to an angle of 360 degrees in the flat plane, a coercive force difference appears, that is, an angle where the coercive force is greater and an angle where the coercive force is smaller, and this is considered to be "having a coercive force difference". FIG. 5 is a schematic diagram showing the direction in which the coercive force is measured by changing the direction every 22.5 degrees with respect to an angle of 360 degrees in the flat plane of the flat magnetic metal particle in the magnetic wedge of the first embodiment. In addition, in FIG. 5, the flat plane of the flat magnetic metal particle is illustrated as seen from above. By having a coercive force difference in the flat plane, the minimum coercive force value becomes smaller, which is preferable compared to the isotropic case where there is almost no coercive force difference. In a material having magnetic anisotropy in the flat plane, the coercive force varies depending on the direction in the flat plane, and the minimum coercive force value is smaller than that of a magnetically isotropic material. This reduces hysteresis loss and improves magnetic permeability, which is preferable. In FIG. 5, a flat magnetic metal particle 10 and a flat plane 6 are shown.
[0020] The flat magnetic metal particles also have a magnetic metal phase containing at least one first element selected from the group consisting of Fe, Co, and Ni. The flat magnetic metal particles contain Fe and Co, and the amount of Co is preferably 10 atomic % or more and 60 atomic % or less relative to the total amount of Fe and Co, and more preferably 10 atomic % or more and 40 atomic % or less. This is preferable because it is easy to impart a moderately large magnetic anisotropy and improves the above-mentioned magnetic properties. In addition, the Fe-Co system is preferable because it is easy to realize high saturation magnetization. Furthermore, it is preferable that the composition range of Fe and Co falls within the above range, because a higher saturation magnetization can be realized.
[0021] The elements can be easily analyzed by EDX (Energy Dispersive X-ray spectroscopy) or ICP (Inductively Coupled Plasma) optical emission spectroscopy.
[0022] The flat magnetic metal particles preferably contain at least one non-magnetic metal selected from the group consisting of Mg, Al, Si, Ca, Zr, Ti, Hf, Zn, Mn, Ba, Sr, Cr, Mo, Ag, Ga, Sc, V, Y, Nb, Pb, Cu, In, Sn, and rare earth elements. This can improve the thermal stability and oxidation resistance of the flat magnetic metal particles. Among them, Al and Si are particularly preferred because they are easily dissolved in Fe, Co, and Ni, which are the main components of the flat magnetic metal particles, and contribute to improving the thermal stability and oxidation resistance.
[0023] In order to induce magnetic anisotropy, there is also a method of making the crystallinity of the flat magnetic metal particles as amorphous as possible, and inducing magnetic anisotropy in one direction in the plane by a magnetic field or distortion. In this case, it is desirable to make the composition of the flat magnetic metal particles as easy to make amorphous as possible. From this point of view, it is preferable that the magnetic metal contained in the flat magnetic metal particles contains at least one additive element selected from B (boron), Si (silicon), Al (aluminum), C (carbon), Ti (titanium), Zr (zirconium), Hf (hafnium), Nb (niobium), Ta (tantalum), Mo (molybdenum), Cr (chromium), Cu (copper), W (tungsten), P (phosphorus), N (nitrogen), Ga (gallium), and Y (yttrium). It is preferable that the additive element has a large difference from the atomic radius of at least one first element selected from the group consisting of Fe, Co, and Ni. In addition, the additive element is preferably one that has a large negative mixing enthalpy between at least one first element selected from the group consisting of Fe, Co, and Ni and the additive element. In addition, it is preferable that the system is a multi-element system consisting of three or more elements in total, including the first element and the additive element. In addition, semimetallic additive elements such as B and Si have a slow crystallization rate and are easily amorphized, so it is advantageous to mix them into the system. From the above perspective, B, Si, P, Ti, Zr, Hf, Nb, Y, Cu, etc. are preferable, and it is more preferable that the additive element contains any one of B, Si, Zr, Hf, and Y. For example, it is preferable that the first element of the magnetic metal phase contains Fe and Co, and the additive element contains Si and B. In addition, it is preferable that the total amount of the additive element is 0.001 at% or more and 80 at% or less with respect to the total amount of the first element and the additive element. More preferably, it is 5 at% or more and 80 at% or less, and even more preferably, it is 10 at% or more and 40 at% or less. In addition, the larger the total amount of the added elements, the more the amorphous state progresses and the easier it is to impart magnetic anisotropy, which is preferable (i.e., it is preferable from the viewpoint of low loss and high magnetic permeability), but on the other hand, it is not preferable because the proportion of the magnetic metal phase decreases, which reduces the saturation magnetization. For the above reasons, it is important to select the composition and the amount of added elements by comprehensively considering high saturation magnetization, low loss, high magnetic permeability, etc.
[0024] It is preferable that at least a portion of the surface of the flat magnetic metal particles is covered with a coating layer having a thickness of 0.1 nm or more and 1 μm or less and containing at least one second element selected from the group consisting of oxygen (O), carbon (C), nitrogen (N) and fluorine (F).
[0025] 6 is a schematic diagram of a flat magnetic metal particle in the magnetic wedge of the first embodiment, showing a coating layer 9 and a flat magnetic metal particle 10.
[0026] It is more preferable that the coating layer contains at least one non-magnetic metal selected from the group consisting of Mg, Al, Si, Ca, Zr, Ti, Hf, Zn, Mn, Ba, Sr, Cr, Mo, Ag, Ga, Sc, V, Y, Nb, Pb, Cu, In, Sn, and rare earth elements, and contains at least one second element selected from the group consisting of oxygen (O), carbon (C), nitrogen (N) and fluorine (F). As the non-magnetic metal, Al and Si are particularly preferable from the viewpoint of thermal stability. When the flat magnetic metal particles contain at least one non-magnetic metal selected from the group consisting of Mg, Al, Si, Ca, Zr, Ti, Hf, Zn, Mn, Ba, Sr, Cr, Mo, Ag, Ga, Sc, V, Y, Nb, Pb, Cu, In, Sn, and rare earth elements, it is more preferable that the coating layer contains at least one non-magnetic metal that is the same as the non-magnetic metal that is one of the components of the flat magnetic metal particles. Among oxygen (O), carbon (C), nitrogen (N) and fluorine (F), it is preferable that the material contains oxygen (O), and it is preferable that the material is an oxide or a composite oxide. The above is from the viewpoint of ease of forming the coating layer, oxidation resistance, and thermal stability. As a result, the adhesion between the flat magnetic metal particles and the coating layer can be improved, and it is possible to improve the thermal stability and oxidation resistance of the magnetic wedge described later. The coating layer can not only improve the thermal stability and oxidation resistance of the flat magnetic metal particles, but also improve the electrical resistance of the flat magnetic metal particles. By increasing the electrical resistance, it is possible to suppress eddy current loss and improve the frequency characteristics of magnetic permeability. For this reason, it is preferable that the coating layer has a high electrical resistance, and it is preferable that the coating layer has a resistance value of, for example, 1 mΩ·cm or more.
[0027] The presence of the coating layer is also preferable from a magnetic point of view. The flat magnetic metal particles can be regarded as a pseudo-thin film because the thickness of the flat magnetic metal particles is small compared to the size of the flat surfaces. In this case, the coating layer formed on the surface of the flat magnetic metal particles and integrated can be regarded as a pseudo-laminated thin film structure, and the magnetic domain structure is energetically stabilized. This makes it possible to reduce the coercive force (thereby reducing hysteresis loss), which is preferable. In this case, the magnetic permeability is also increased, which is preferable. From this point of view, it is more preferable that the coating layer is non-magnetic (the magnetic domain structure is more easily stabilized).
[0028] From the viewpoints of thermal stability, oxidation resistance, and electrical resistance, the thicker the coating layer, the better. However, if the coating layer is too thick, the saturation magnetization decreases, which is undesirable as the magnetic permeability also decreases. Also, from a magnetic viewpoint, if the thickness is too thick, the "effect of stabilizing the magnetic domain structure to achieve low coercive force, low loss, and high magnetic permeability" decreases. Taking the above into consideration, the preferred thickness of the coating layer is 0.1 nm to 1 μm, and more preferably 0.1 nm to 100 μm.
[0029] The intervening phase contains at least one second element selected from the group consisting of oxygen (O), carbon (C), nitrogen (N) and fluorine (F). This is because it is possible to increase the electrical resistance. The electrical resistivity of the intervening phase is preferably higher than that of the flat magnetic metal particles. This is because it is possible to reduce the eddy current loss of the flat magnetic metal particles. Since the intervening phase exists surrounding the flat magnetic metal particles, it is preferable that it can improve the oxidation resistance and thermal stability of the flat magnetic metal particles. Among these, those containing oxygen are more preferable from the viewpoint of high oxidation resistance and high thermal stability. Since the intervening phase also plays a role of mechanically bonding the flat magnetic metal particles together, it is also preferable from the viewpoint of high strength.
[0030] The intervening phase preferably contains a resin. As the resin, a thermoplastic resin, a thermosetting resin, a polyester resin, a vinyl ester resin, a polyethylene resin, a polystyrene resin, a polyvinyl chloride resin, a polyvinyl butyral resin, a polyvinyl alcohol resin, a polybutadiene resin, a Teflon (registered trademark) resin, a polyurethane resin, a cellulose resin, an ABS resin, a nitrile-butadiene rubber, a styrene-butadiene rubber, a silicone resin, other synthetic rubber, a natural rubber, an epoxy resin, a phenol resin, an allyl resin, a polybenzimidazole resin, an amide resin, a polyimide resin, a polyamideimide resin, a bismaleimide resin, or a copolymer thereof is used. In particular, in order to realize high thermal stability, it is preferable to contain a silicone resin, a polyimide resin, an imide resin, or a bismaleimide resin, which have high heat resistance. Epoxy resin, phenol resin, and polyester resin are relatively high heat resistance and high strength, and are general-purpose resins, and are preferable. It is also preferable that the material contains at least one resin selected from the group consisting of bismaleimide resin, polyimide resin, polyester resin, phenol resin, epoxy resin, and silicone resin. It is also preferable that the weight increase rate after exposure to 120°C for 30 minutes in the atmosphere and then exposure to room temperature in the atmosphere for one week is 1% or less, more preferably 0.1% or less. It is also preferable that the water absorption rate defined by ISO 62:1999 (JIS K7209:2000) is 1% or less, more preferably 0.1% or less. In order to increase the strength, materials such as FRP (Fiber-Reinforced Plastics) containing fibers such as glass fiber, aramid fiber, carbon fiber, Zylon fiber, polyethylene fiber, and boron fiber are also preferable. As a result, the bond between the flat magnetic metal particles and the intervening phase becomes stronger, and mechanical properties such as thermal stability, strength, and toughness are easily improved. In addition, since the intervening phase surrounds the flat magnetic particles, the flat magnetic metal particles have excellent oxidation resistance and are less susceptible to deterioration of magnetic properties due to oxidation, which is preferable. The type of resin can be identified by IR (Infrared Spectroscopy), NMR (Nuclear Magnetic Resonance), etc.
[0031] Bismaleimide resins are preferred because the molding temperature can be kept relatively low (for example, 180°C or lower), and therefore molding can be performed using a general-purpose low-temperature hot press device. In addition, they are preferred because they can achieve high thermal stability and excellent mechanical properties after molding. Furthermore, they are easily composited (bonded) with flat magnetic metal particles, and are preferred because they can easily achieve excellent properties in terms of thermal stability as a composite material and mechanical properties such as strength and toughness. In addition, they are preferred because the intervening phase easily surrounds the flat magnetic particles, and deterioration of the magnetic properties due to oxidation of the flat magnetic metal particles is unlikely to occur.
[0032] The bismaleimide resin preferably has a glass transition temperature of 250° C. or higher, which is preferable because it provides high thermal stability and strength.
[0033] Specifically, the bismaleimide resins include 4,4'-diphenylmethane bismaleimide, phenylmethane maleimide, m-phenylene bismaleimide, bisphenol A diphenyl ether bismaleimide, 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide, 4-methyl-1,3-phenylene bismaleimide, 1,6'-bismaleimide-(2,2,4-trimethyl)hexane, 2,2'-diallyl bisphenol A, 4,4'-diphenyl It is preferable that the monomer contains aryl ether bismaleimide, 4,4'-diphenylsulfone bismaleimide, 1,3-bis(3-maleimidophenoxy)benzene, 1,3-bis(4-maleimidophenoxy)benzene, bis(3-ethyl-5-methyl-4-maleimidophenyl)methane, 2,2'-bis[4-(4-maleimidophenoxy)phenyl]propane, etc. (These monomers are polymerized to produce bismaleimide resins, so it is preferable to contain the above as monomers.) This increases the thermal stability and strength, etc., and is therefore preferable.
[0034] In addition, the curing agent for curing the monomer preferably includes 4,4'-diaminodiphenylmethane, diaminodiphenyl ether, diaminodiphenyl sulfone, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, o,o'-diallyl bisphenol A, etc. However, the curing agent may be of any other type as long as it can appropriately cure the monomer.
[0035] A preferred combination of monomer and curing agent is, for example, 4,4'-diphenylmethane bismaleimide and 4,4'-diaminodiphenylmethane. In addition, when 4,4'-diphenylmethane bismaleimide and 4,4'-diaminodiphenylmethane are contained, the ratio of 4,4'-diphenylmethane bismaleimide to 4,4'-diaminodiphenylmethane is preferably 1 to 3, more preferably about 2. By having the above ratio, thermal stability and strength are increased, which is preferable.
[0036] The molecular weight of the intervening phase is preferably from 100 to 1000. This is preferable because it increases the thermal stability and strength.
[0037] The polyimide resin preferably contains a repeating unit represented by the following chemical formula (1). [ka] (1) In the chemical formula (1), R preferably contains any one of a biphenyl, triphenyl, and tetraphenyl structure, and R' preferably represents a structure having at least one aromatic ring therein.
[0038] Moreover, the polyimide resin more preferably has the following structural formula (2) or (3). [ka] (2) [ka] (3)
[0039] FIG. 7 is a schematic diagram of the magnetic wedge of this embodiment. As shown in FIG. 7, the magnetic wedge may have not only a simple rectangular parallelepiped shape (with a rectangular cross section), but also various shapes such as a trapezoid, hexagon, or convex cross section. The closer the magnetic wedge is placed to the gap surface between the rotor and the stator, the more effective it is (the effect of improving the efficiency of the rotating electric machine). From this viewpoint, the trapezoid, convex, and hexagonal shapes are more preferable than the rectangular shape. Also, from the viewpoint of "a shape that easily draws magnetic flux into the magnetic wedge (thereby making it easier to improve the efficiency of the rotating electric machine)", the trapezoid and convex shapes are more preferable than the hexagonal shape. On the other hand, from the viewpoints of ease of manufacture and high reliability as a material (mechanical properties, thermal properties), the rectangular shape is most preferable, followed by the trapezoid and hexagonal shapes. In this sense, the trapezoidal type is highly preferable because it can be easily placed close to the gap surface between the rotor and stator, and the trapezoidal shape makes it easy to draw the magnetic flux toward the magnetic wedge side.Furthermore, it is easy to manufacture and easy to increase the reliability of the material (mechanical properties, thermal properties).
[0040] Regardless of the shape, the three axial directions that intersect perpendicularly or orthogonally to each other are defined as the width direction, thickness direction, and longitudinal direction. The longitudinal direction of the magnetic wedge is the direction in which the length of the magnetic wedge is longer. For example, when the shape of the target magnetic wedge is an approximately rectangular parallelepiped shape, the direction along the longest side of the approximately rectangular parallelepiped shape is determined as the longitudinal direction of the target magnetic wedge. The thickness direction and width direction of the magnetic wedge are directions perpendicular to the longitudinal direction of the magnetic wedge. The thickness direction and width direction of the magnetic wedge can be distinguished as follows. When the target magnetic wedge is provided in a rotating electric machine, the target magnetic wedge is taken out from inside the rotating electric machine. Here, the rotation direction of the rotating electric machine is the width direction of the target magnetic wedge. The thickness direction is the direction perpendicular to the width direction. On the other hand, when the target magnetic wedge is not provided in a rotating electric machine, the direction closest to the average orientation direction of the flat magnetic metal particles at the center of the cross section perpendicular to the longitudinal direction is the width direction. The thickness direction is perpendicular to the width direction. For the cross section perpendicular to the longitudinal direction, the end face of the target magnetic wedge is avoided. For such a cross section, the target magnetic wedge is cut perpendicular to the longitudinal direction of the target magnetic wedge so that the length of the cross section is at least one tenth of the longitudinal length of the target magnetic wedge. In addition, as the center of the cross section formed by cutting, for example, a region containing multiple flat magnetic metal particles at the geometric center of the cross section is used. Next, the cross section formed by cutting the target magnetic wedge is observed using an optical microscope, SEM, or TEM. Then, for each flat magnetic metal particle observed in the cross section formed by cutting, the rectangle with the smallest area among the rectangles circumscribing each flat magnetic metal particle is considered, and the direction of the long side direction of the rectangle is measured as the orientation direction. However, some flat magnetic metal particles may have an unclear particle outline during observation and are difficult to evaluate. In other words, there are cases where the particle outline cannot be clearly identified by image analysis, and in such cases, the particle is excluded from the observation target.
[0041] FIG. 8 is a schematic diagram of a magnetic wedge according to the present embodiment. In a cross section perpendicular to the longitudinal direction of the magnetic wedge at the center of the longitudinal direction (hereinafter, the characteristics are defined for this cross section), flat magnetic metal particles existing near the widthwise contour line and flat magnetic metal particles existing closer to the center of the magnetic wedge are shown. Note that, as a method for determining the cross section perpendicular to the longitudinal direction of the magnetic wedge at the center of the longitudinal direction, any method can be used as long as it can determine the size and contour line of the flat magnetic metal particles. For example, the observation is performed using a scanning electron microscope (SEM: Scanning Electron Microscopy), an optical microscope, or a transmission electron microscope (TEM: Transmission Electron Microscopy), and the like, at any magnification. Here, the flat magnetic metal particles existing closest to the widthwise contour line are referred to as flat magnetic metal surface particles. In addition, the widthwise contour average line is an average line obtained by averaging the unevenness of the widthwise contour line. The contour mean line can be defined as, for example, the "mean line" in the surface roughness measurement of JIS-B0601 (ISO-4287). In the magnetic wedge of this embodiment, it is preferable that the flat magnetic metal surface particles are arranged outside the contour mean line in the width direction in a cross section perpendicular to the longitudinal direction of the magnetic wedge and at the center of the longitudinal direction, with 10% or more of the length of the flat magnetic metal particles being arranged outside the contour mean line in the width direction of the magnetic wedge. More preferably, the flat magnetic metal surface particles arranged outside the contour mean line in the width direction of the magnetic wedge in a cross section perpendicular to the longitudinal direction of the magnetic wedge and at the center of the longitudinal direction are preferably included in the total number of flat magnetic metal surface particles present in the measured cross section, more preferably 1% to 90%, more preferably 5% to 60%, and even more preferably 5% to 30%.
[0042] In a cross section perpendicular to the longitudinal direction of the magnetic wedge and at the center of the longitudinal direction, the orientation angle of the flat magnetic metal surface particles, of which 10% or more of their length is positioned outside the widthwise contour average line of the magnetic wedge, is preferably 1 degree or more and 60 degrees or less with respect to the widthwise contour average line, more preferably 3 degrees or more and 45 degrees or less, and even more preferably 3 degrees or more and 30 degrees or less.
[0043] As examples of flat magnetic metal surface particles in which 10% or more of the length is arranged outside the average contour line in the width direction of the magnetic wedge, flat magnetic metal surface particles A and B are shown in FIG. 8. For both flat magnetic metal surface particles A and B, 10% or more of the length of the flat magnetic metal particle is located outside the average contour line in the width direction of the magnetic wedge. A portion of flat magnetic metal surface particle A is arranged protruding outside the magnetic wedge, while flat magnetic metal particle B does not protrude outside the magnetic wedge and is arranged within the intervening phase. Either flat magnetic metal surface particle A or B is preferable.
[0044] The flat magnetic metal particles of the magnetic wedge have the above-mentioned arrangement structure, so that the surface roughness is moderately rough. The surface roughness Ra of the magnetic wedge is 0.1 μm or more and 100 μm or less, more preferably 0.1 μm or more and 10 μm or less, and even more preferably 1 μm or more and 10 μm or less. It is preferable that the widthwise contour line (i.e., the widthwise surface) of the cross section perpendicular to the longitudinal direction of the magnetic wedge at the center of the longitudinal direction meets this surface roughness range, but it is more preferable that the surface of the magnetic wedge including the widthwise and lengthwise directions meets this surface roughness range, and even more preferable that any surface of the magnetic wedge meets this surface roughness range. The surface roughness Ra and its measurement method are defined in JIS-B0601 (ISO-4287).
[0045] By having the above-mentioned structure (the arrangement structure, number ratio, orientation angle, surface roughness, etc. of the flat magnetic metal surface particles), the magnetic flux can be efficiently guided in the rotating electric machine, and the magnetic permeability and efficiency of the rotating electric machine are improved, which is preferable. Regarding the magnetic permeability, it is preferable because the magnetic permeability is improved in the direction intermediate between the width direction and the thickness direction of the magnetic wedge. In addition, the loss is also reduced in the direction intermediate between the width direction and the thickness direction of the magnetic wedge, which is preferable.
[0046] Furthermore, by having the above-mentioned structure, when a surface coating layer for protecting the magnetic wedge is further provided, an anchoring effect can be obtained, so that the coating layer can be formed firmly. This is preferable because it improves the reliability of the material. For example, it is preferable because it can maintain excellent characteristics without deteriorating the strength after heat resistance testing and the efficiency as a rotating electric machine.
[0047] FIG. 9 is a cross-sectional photograph of a magnetic wedge according to the present embodiment. Examples are shown in FIG. 9(a) and FIG. 9(b). FIG. 9(a) shows flat magnetic metal particles with an orientation angle of 23 degrees, 64% of which are arranged outside the widthwise contour average line, flat magnetic metal particles with an orientation angle of 14 degrees, 62% of which are arranged outside the widthwise contour average line, and flat magnetic metal particles with an orientation angle of 15 degrees, 79% of which are arranged outside the widthwise contour average line. FIG. 9(b) shows flat magnetic metal particles with an orientation angle of 5 degrees, 27% of which are arranged outside the widthwise contour average line, and flat magnetic metal particles with an orientation angle of 8 degrees, 23% of which are arranged outside the widthwise contour average line. These are examples of flat magnetic metal surface particles with 10% or more of the length of the flat magnetic metal particles arranged outside the widthwise contour average line. The orientation angle of these flat magnetic metal surface particles is from 1 degree to 60 degrees (also from 3 degrees to 30 degrees) relative to the average line of the profile in the width direction.
[0048] Fig. 10 is a schematic diagram of the magnetic wedge of this embodiment. In Fig. 10, at least a part of the surface of the magnetic wedge is covered with a surface coating layer. In this case, it is more preferable that at least a part of the flat magnetic metal surface particle is covered with a surface coating layer. That is, it is preferable that at least a part of the flat magnetic metal surface particle A in Fig. 8 is covered with a surface coating layer.
[0049] The thickness of the surface coating layer is preferably equal to or greater than the average thickness of the flat magnetic metal surface particles, and more preferably equal to or greater than the average length of the flat magnetic metal particles. More preferably, the thickness is equal to or greater than the maximum length of the flat magnetic metal particles. By having the above structure, the surface coating layer is preferably firmly attached (bonded) to the magnetic wedge (anchor ring effect) and can protect the magnetic wedge. This is preferable because it can improve the reliability of the material. For example, the presence of the coating layer can significantly improve the electrical resistivity, so that when used as a magnetic wedge, electrical short circuits can be suppressed, and eddy current losses can be reduced to improve the efficiency of a rotating electric machine, which is preferable. In addition, it is preferable because it can maintain excellent characteristics without deteriorating the strength after a heat resistance test and the efficiency as a rotating electric machine. In addition, it is preferable because it can suppress oxidation of the flat magnetic metal particles and the flat magnetic metal surface particles, and can maintain excellent magnetic properties (saturation magnetization, coercive force, and magnetic permeability).
[0050] The surface coating layer preferably contains inorganic materials such as oxides, carbides, nitrides, and borides, or organic materials such as resins, but more preferably contains resins. Examples of resins include thermoplastic resins, thermosetting resins, polyester resins, vinyl ester resins, polyethylene resins, polystyrene resins, polyvinyl chloride resins, polyvinyl butyral resins, polyvinyl alcohol resins, polybutadiene resins, Teflon (registered trademark) resins, polyurethane resins, cellulose resins, ABS resins, nitrile-butadiene rubbers, styrene-butadiene rubbers, silicone resins, other synthetic rubbers, natural rubbers, epoxy resins, phenolic resins, allyl resins, polybenzimidazole resins, amide resins, polyimide resins, polyamideimide resins, bismaleimide resins, and copolymers thereof. In particular, in order to achieve high thermal stability, it is preferable to contain silicone resins, polyimide resins, imide resins, and bismaleimide resins, which have high heat resistance. Epoxy resins, phenolic resins, and polyester resins are relatively high heat resistance, high strength, and versatile resins, and are therefore preferable. In addition, it is preferable that the resin composition contains at least one resin selected from the group consisting of bismaleimide-based resins, polyimide-based resins, polyester-based resins, phenol-based resins, epoxy-based resins, and silicone-based resins.
[0051] As mentioned above, the type of resin can be identified by IR, NMR, etc. In addition, it is preferable that the weight increase rate after exposure to 120°C air for 30 minutes and then to room temperature air for one week is 1% or less, more preferably 0.1% or less. In addition, it is preferable that the water absorption rate defined by ISO 62:1999 (JIS K7209:2000) is 1% or less, more preferably 0.1% or less. In a magnetic wedge consisting of flat magnetic metal particles and an intervening phase, it was found by a preliminary investigation that when the intervening phase is resin, the weight increases and mechanical properties such as strength tend to deteriorate when it absorbs moisture or humidity. In addition, when the flat magnetic metal particles absorb moisture or humidity, oxidation occurs, the saturation magnetization and magnetic permeability decrease, and loss also increases, which is not preferable. Therefore, it is considered effective to prevent moisture or humidity from coming into contact with the intervening phase as much as possible (to suppress weight increase). In this embodiment, the surface of the magnetic wedge is coated with a surface coating layer with low water absorption and hygroscopicity, so that it is possible to prevent water and moisture from coming into contact with the intervening phase as much as possible. This makes it possible to maintain excellent properties without deteriorating mechanical properties such as strength. In addition, oxidation of the flat magnetic metal particles is suppressed, so that excellent properties can be maintained without deteriorating saturation magnetization, magnetic permeability, and loss.
[0052] A method for manufacturing the magnetic wedge of this embodiment will be described below. Note that the manufacturing method is not particularly limited and will be described merely as an example.
[0053] The first step is a step of manufacturing a magnetic metal ribbon containing at least one first element selected from the group consisting of Fe, Co, and Ni. This step is a step of manufacturing a ribbon or a thin film using a film-forming device such as a roll quenching device or a sputtering device. In this case, in the film-forming method using the film-forming device, it is desirable to form a film with uniaxial anisotropy in the film surface by film-forming in a magnetic field or rotational film-forming. In addition, when using a film-forming device, the thickness can be made thin, the structure is likely to be refined, and rotational magnetization is likely to occur, so it is desirable to use the film-forming method when making a rotational magnetization type. The roll quenching device is suitable for mass synthesis, so it is desirable when synthesizing a bulk material. In the case of a roll quenching device, a single roll quenching device is simple and preferable.
[0054] The second step is a step of heat treating the magnetic metal ribbon at a temperature of 50°C or more and 800°C or less. In this step, the ribbon may be cut to an appropriate size so that it can be easily put into an electric furnace for heat treatment. For example, it may be cut to an appropriate size using a mixer device or the like. By performing this step, it is preferable that the crushability is improved in the next third step, which is the crushing step. The heat treatment atmosphere is preferably a vacuum atmosphere with a low oxygen concentration, an inert atmosphere, or a reducing atmosphere, and more preferably a reducing atmosphere such as H2 (hydrogen), CO (carbon monoxide), or CH4 (methane). The reason for this is that even if the magnetic metal ribbon is oxidized, by performing heat treatment in a reducing atmosphere, it is possible to reduce the oxidized metal and return it to metal. This makes it possible to reduce a magnetic metal ribbon that has been oxidized and has a reduced saturation magnetization, and to restore the saturation magnetization. In the case of an amorphous composition, if the crystallization of the magnetic metal ribbon proceeds significantly due to heat treatment, the coercive force increases and the magnetic permeability decreases, so it is preferable to select conditions to suppress excessive crystallization. More preferably, the heat treatment is performed in a magnetic field. The larger the magnetic field to be applied, the better, but it is preferable to apply 1 kOe or more, and even more preferably 10 kOe or more. This is preferable because it is possible to express magnetic anisotropy in the plane of the magnetic metal ribbon and realize excellent magnetic properties.
[0055] The third step is a step of producing flat magnetic metal particles by pulverizing the heat-treated magnetic metal ribbon. In this step, the magnetic metal ribbon or thin film may be cut to an appropriate size using a mixer or the like before the pulverization. In this step, the pulverization is performed using a pulverization device such as a bead mill or a planetary mill. The pulverization device may be of any type. For example, a planetary mill, a bead mill, a rotary ball mill, a vibration ball mill, an agitating ball mill (attritor), a jet mill, a centrifuge, or a method combining a mill and centrifugation may be used. During pulverization, it is preferable to perform pulverization while cooling at a temperature of 0°C or lower, since this makes it easier to proceed with pulverization. In particular, it is preferable to cool at a liquid nitrogen temperature (77K) or a dry ice temperature (194K), and among these, it is more preferable to cool to the liquid nitrogen temperature. This makes the magnetic metal ribbon more likely to become brittle at low temperatures, making pulverization easier. In other words, this is preferable because pulverization can be performed efficiently without applying excessive stress or distortion to the magnetic metal ribbon. However, in many cases, the powder can be pulverized sufficiently without cooling, in which case cooling is not necessary.
[0056] In the third step, the thickness of the flat magnetic metal particles can be reduced by combining rolling with simple pulverization. If the thickness is already at a predetermined level by the second step, the rolling process can be omitted. Here, rolling may be performed simultaneously, or rolling may be performed after pulverization, or pulverization may be performed after rolling. In this case, a device capable of applying strong gravitational acceleration is preferred, and examples of such devices include planetary mills, bead mills, rotary ball mills, vibrating ball mills, stirring ball mills (attritors), jet mills, centrifuges, or a combination of mills and centrifugation. For example, a high-power planetary mill device is preferred because it can easily apply gravitational accelerations of several tens of G. In the case of a high-power planetary mill device, an inclined planetary mill device is more preferred, in which the direction of the rotational gravitational acceleration and the direction of the revolutionary gravitational acceleration are not in the same straight line but are in an angled direction. In a normal planetary mill, the direction of the gravitational acceleration due to rotation and the direction of the gravitational acceleration due to revolution are on the same line, but in an inclined planetary mill, the container rotates while being tilted, so the direction of the gravitational acceleration due to rotation and the direction of the gravitational acceleration due to revolution are not on the same line but at an angle. This is preferable because power is efficiently transmitted to the sample, and pulverization and rolling proceed efficiently. In addition, when considering mass production, a bead mill is preferable because it is easy to process large quantities.
[0057] It is desirable to carry out the above cutting, crushing and rolling (rolling is carried out as necessary, and not carried out if not necessary), and in some cases to repeat the cutting, crushing and rolling processes to process the particles into flat magnetic metal particles of a predetermined thickness and aspect ratio. At this time, it is preferable to carry out crushing and rolling so that the thickness is 10 nm to 100 μm, more preferably 10 nm to 1 μm, and even more preferably 10 nm to 100 nm, since this results in particles that are prone to rotational magnetization.
[0058] In order to realize the degree of orientation of the flat magnetic metal particles as in the present embodiment, it is effective to improve the slippage of the flat magnetic metal particles and increase the fluidity. Therefore, it is preferable that the average thickness of the flat magnetic metal particles is 10 μm or more and 30 μm or less, more preferably 10 μm or more and 20 μm or less, and the average value of the ratio of the average length to the thickness of the flat magnetic metal particles is 10 to 100 or less, more preferably 10 to 50 or less.
[0059] It is also desirable to remove the lattice distortion of the obtained flat magnetic metal particles by heat treatment to an appropriate degree. The heat treatment is preferably carried out at a temperature of 50°C or higher and 800°C or lower, as in the second step, and the heat treatment atmosphere is preferably a vacuum atmosphere with a low oxygen concentration, an inert atmosphere, or a reducing atmosphere, and more preferably a reducing atmosphere such as H2, CO, or CH4. It is more desirable to carry out the heat treatment in a magnetic field. The reasons and details of these are the same as those in the second step, so they will not be explained here.
[0060] Next, in the fourth step, the above-mentioned intervening phase and magnetic metal particles are mixed to form a mixed powder of the intervening phase and flat magnetic metal particles. Next, in the fifth step, the mixed powder of the intervening phase and magnetic metal particles is molded. Also, heat treatment may be performed before or after the above steps as appropriate. That is, heat treatment may be performed before or after molding, or at the same time as molding. Also, heat treatment may be performed before or after processing. The heat treatment conditions are as described above. Also, it is more preferable to perform heat treatment in a magnetic field. The reasons and details of these are the same as those in the second step, so explanations will be omitted here.
[0061] In order to obtain the magnetic wedge of this embodiment, this fifth step is very important. In this fifth step, it is preferable to use a method of applying a press pressure in a uniaxial direction, such as uniaxial press molding or hot press molding. When a press pressure is applied in a uniaxial direction, the flat magnetic metal particles tend to be layered and oriented in the direction of the press pressure application. Therefore, in a simple uniaxial press molding, the flat magnetic metal particles are layered and oriented in the direction of the press pressure application, that is, in one direction, which is not very preferable. Therefore, when applying a press pressure in a uniaxial direction, it is preferable to apply a magnetic field in a direction parallel to the direction of the press pressure application. It is also preferable to magnetize the die punch during molding in a direction parallel to the direction of the press pressure application. As a result, the flat magnetic metal particles are more likely to move in a direction parallel to the direction of the press pressure application, making it easier to synthesize a magnetic wedge that includes flat magnetic metal surface particles that are arranged outside the average contour line in the width direction of the magnetic wedge for 10% or more of their length. In addition, the ratio of flat magnetic metal surface particles whose length is 10% or more outside the average contour line in the width direction of the magnetic wedge to the total number of flat magnetic metal surface particles can be adjusted by changing the magnetic field application conditions, mold state, and press conditions.
[0062] In addition, it is preferable to perform hot press molding after uniaxial press molding. When the intervening phase is, for example, a thermosetting resin, it is preferable to adjust the hot press temperature and time in hot press molding and stop before the intervening phase hardens. In addition, it is more preferable to perform hot press while applying a magnetic field in a direction parallel to the direction of application of the press pressure. This makes it easier for the flat magnetic metal particles to move in a direction parallel to the direction of application of the press pressure, making it easier to synthesize "magnetic wedges including flat magnetic metal surface particles with 10% or more of their length arranged outside the average contour line in the width direction of the magnetic wedge". In addition, it is also preferable to reduce or release the press pressure when the resin is softened and melted during hot press. This is preferable because it makes it easier for the flat magnetic metal particles to move in a direction parallel to the direction of application of the press pressure. The hot press temperature is preferably 50°C or more and 1000°C or less, more preferably 50°C or more and 800°C or less. The stronger the magnetic field to be applied, the more preferable, but it is preferable to apply 1 kOe or more, and more preferably 10 kOe or more. The pressing pressure is preferably 1 MPa or more and 100 MPa or less, and more preferably 1 MPa or more and 10 MPa or less. It is then preferable to perform heat treatment while applying a magnetic field in a direction parallel to the pressing pressure application direction, and to completely harden the material. The heat treatment temperature is preferably 50°C or more and 1000°C or less, and more preferably 50°C or more and 800°C or less. The stronger the magnetic field to be applied, the more preferable, but it is preferable to apply 1 kOe or more, and more preferably 10 kOe or more.
[0063] By adjusting the hot pressing temperature and time, it is possible to adjust the "ratio of flat magnetic metal surface particles that are arranged outside the average contour line in the width direction of the magnetic wedge for 10% or more of their length to the total number of flat magnetic metal surface particles." For example, if you want to increase the "ratio of flat magnetic metal surface particles that are arranged outside the average contour line in the width direction of the magnetic wedge for 10% or more of their length to the total number of flat magnetic metal surface particles," you can adjust it by lowering the hot pressing temperature or shortening the hot pressing time. By lowering the hot pressing temperature or shortening the hot pressing time, the intervening phase is not sufficiently hardened, and the flat magnetic metal particles become more mobile. As a result, when heat treatment is performed while applying a magnetic field parallel to the direction of application of the press pressure after hot pressing, the flat magnetic metal particles become more likely to move in the direction parallel to the direction of application of the press pressure (hardening while moving), and as a result, after the intervening phase is completely hardened, the "ratio of the flat magnetic metal surface particles that are arranged outside the average contour line in the width direction of the magnetic wedge for 10% or more of their length to the total number of flat magnetic metal surface particles" increases. Conversely, if you want to reduce the "ratio of the flat magnetic metal surface particles that are arranged outside the average contour line in the width direction of the magnetic wedge for 10% or more of their length to the total number of flat magnetic metal surface particles," you can adjust it by increasing the hot pressing temperature or lengthening the hot pressing time. By increasing the hot pressing temperature or lengthening the hot pressing time, the hardening of the intervening phase progresses more, and the flat magnetic metal particles become less likely to move. As a result, when heat treatment is performed after hot pressing while applying a magnetic field in a direction parallel to the direction of application of the pressing pressure, the flat magnetic metal particles are less likely to move in a direction parallel to the direction of application of the pressing pressure (hardening while remaining in a state where they are less likely to move), and as a result, after the intervening phase has completely hardened, "the ratio of flat magnetic metal surface particles that are arranged outside the average contour line in the width direction of the magnetic wedge with 10% or more of their length to the total number of flat magnetic metal surface particles" becomes smaller. Even if the intervening phase is a thermoplastic resin or an oxide with a softening point, it is possible to manufacture a similar magnetic wedge by devising the molding process. In other words, it is possible to manufacture a similar magnetic wedge regardless of the type of intervening phase.For example, when the resin is softened and melted during hot pressing, it is possible to manufacture a similar magnetic wedge by reducing or releasing the pressing pressure, or by applying a magnetic field parallel to the direction of the pressing pressure, and then lowering the temperature and solidifying it under that condition.
[0064] Next, in the sixth step, a surface coating layer is formed on the surface of the molded magnetic wedge. In this step, an inorganic material or an organic material is coated on the surface of the magnetic wedge. The coating method is not particularly limited. When coating an organic material such as a resin, it is preferable to coat the material by an impregnation method, a dipping method, or the like, or in some cases to press the material with a hot press after coating. When coating an inorganic material, it is preferable to coat the material by a gas phase method or a liquid phase method such as sol-gel, or in some cases to press the material with a hot press after coating. It is also preferable to perform a heat treatment after coating to form a strong coating layer.
[0065] When measuring the coercive force depending on the direction within a plane parallel to the flat surfaces of the flat magnetic metal particles of the magnetic wedge, for example, the coercive force is measured by changing the direction every 22.5 degrees over an angle of 360 degrees within the plane.
[0066] By having a coercivity difference in the plane of the magnetic wedge, the minimum coercivity value is smaller than in the case of isotropy where there is almost no coercivity difference, which is preferable. In a material having magnetic anisotropy in a plane, the coercivity differs depending on the direction in the plane, and the minimum coercivity value is smaller than in a magnetically isotropic material. This reduces hysteresis loss and improves magnetic permeability, which is preferable.
[0067] In a plane parallel to the flat surface of the flat magnetic metal particle of the magnetic wedge, the larger the ratio of the coercive force difference due to the direction, the more preferable, and it is preferably 1% or more. More preferably, the ratio of the coercive force difference is 10% or more, even more preferably, the ratio of the coercive force difference is 50% or more, and even more preferably, the ratio of the coercive force difference is 100% or more. The ratio of the coercive force difference here is defined as (Hc(max)-Hc(min)) / Hc(min)×100(%), using the maximum coercive force Hc(max) and the minimum coercive force Hc(min) in the flat surface.
[0068] The coercive force can be easily evaluated using a vibrating sample magnetometer (VSM) or the like. When the coercive force is low, a coercive force of 0.1 Oe or less can be measured by using a low magnetic field unit. The measurement is performed by changing the direction of the measuring magnetic field within the plane of the magnetic wedge (within a plane parallel to the flat surface of the flat magnetic metal particle).
[0069] When calculating the coercive force, the difference between the magnetic fields at the two points where the magnetization intersects the horizontal axis (magnetic fields H1 and H2 where magnetization is zero) can be divided by 2 (i.e., coercive force = |H2-H1| / 2).
[0070] As described above, according to this embodiment, the magnetic wedge is a magnetic wedge for a rotating electric machine, the magnetic wedge includes a plurality of flat magnetic metal particles and an intervening phase, and includes flat magnetic metal surface particles arranged outside the average contour line in the width direction of the magnetic wedge for 10% or more of their length in a cross section perpendicular to the longitudinal direction of the magnetic wedge and at the center of the longitudinal direction. This makes it possible to provide a magnetic wedge having excellent magnetic properties such as high permeability and low loss, excellent mechanical properties such as strength, and excellent thermomechanical properties such as excellent magnetic properties and mechanical properties even after heat resistance tests.
[0071] (Second embodiment) The rotating electric machine of this embodiment includes the magnetic wedge of the first embodiment. Therefore, the description of the contents overlapping with the first embodiment will be omitted. In this specification, the rotating electric machine means a concept including any of an electric motor (motor), a generator, and a motor-generator that functions as both a motor and a generator as necessary.
[0072] FIG. 11 is an example of a radial gap type motor of this embodiment. The radial gap type motor has a rotor and a stator arranged to face the rotor with a predetermined gap in the radial direction. In FIG. 11, the rotor is arranged inside the stator, but it may be arranged outside. The rotor has a rotor core and a shaft, and is supported so as to be rotatable. On the other hand, the stator has a stator core, a field coil inserted in the slot of the stator core, and a magnetic wedge held in the wedge groove at the slot opening. FIG. 11 shows an example in which the magnetic wedge of the first embodiment is arranged, but is not limited to this. In the case of a radial gap type rotating electric machine, the stator is arranged to face the rotor with a predetermined gap in the radial direction, so that the "gap surface" is a surface parallel to a cylindrical surface centered on the rotation axis of the rotor. Therefore, the radial direction is perpendicular to the gap surface, and the axial direction and the rotation direction are parallel to the gap surface. In FIG. 11, flat magnetic metal particles 10, intervening phases 20, magnetic wedges 100, a rotating electric machine 200, a rotor 210, a stator 220, a coil 230, a gap surface 240, and iron core teeth 250 are shown.
[0073] By arranging the magnetic wedge of the first embodiment, it is possible to reduce harmonic loss occurring on the rotor surface while suppressing leakage magnetic flux. In addition, the magnetic flux passing through the air gap increases, so the torque of the radial gap motor is increased. High efficiency can be achieved by either or both of the above loss reduction effect and torque increase effect.
[0074] The radial gap motor may be one having a conductor in the rotor (induction motor), one having a permanent magnet (permanent magnet motor), or one having a magnetic body (reluctance motor).
[0075] FIG. 12 is an example of an axial gap motor of this embodiment. The axial gap motor has a rotor and a stator arranged to face the rotor with a predetermined gap in the axial direction, and the stator is provided with a stator core, a field coil inserted in a slot of the stator core, and a magnetic wedge held in a wedge groove at the slot opening. By arranging the magnetic wedge of this embodiment, it is possible to reduce harmonic loss generated on the rotor surface while suppressing an increase in leakage magnetic flux. In addition, since the magnetic flux passing through the gap increases, the torque of the axial gap motor is increased. As a result, high efficiency can be achieved. In FIG. 12, the rotor is arranged between two stators, but it may be arranged on one or both sides of one stator. In the case of an axial gap rotating electric machine, the stator is arranged to face the rotor with a predetermined gap in the axial direction, so the "gap surface" is a surface perpendicular to the rotation axis of the rotor. Therefore, the axial direction is perpendicular to the gap surface, and the rotation direction and the radial direction are parallel to the gap surface. In Fig. 12, flat magnetic metal particles 10, intervening phases 20, magnetic wedges 100, rotating electric machine 200, rotor 210, coil 230, gap surface 240, iron core teeth 250, stator 270, and shaft 280 are shown.
[0076] FIG. 13 is a schematic diagram showing an example of a generator of this embodiment. A generator usually has a rotor that houses an excitation coil in the slots of a rotor core (otherwise, a rotor using a permanent magnet as an excitation source may be adopted) and a stator that houses an armature coil in the slots of a stator core, and generates electric power in the armature coil by rotating the rotor and passing an excitation current through the excitation coil. The rotor includes a rotor core, a field coil inserted in the slots of the rotor core, and a magnetic wedge held in a wedge groove at the opening of the slot, and is supported by a bearing so as to be rotatable. By disposing the magnetic wedge of this embodiment, it is possible to reduce harmonic loss occurring on the surface of the stator while suppressing an increase in leakage magnetic flux. In addition, the magnetic flux that passes through the air gap and interlinks with the armature coil increases, so that the generated voltage induced in the armature coil increases. As a result, high efficiency can be achieved. In FIG. 13, the magnetic wedges are arranged at the slot openings of the rotor core, but they may be arranged at the slot openings of the stator core. In addition, the figure shows a winding type generator with an excitation coil in the rotor, but it may be a permanent magnet type generator with a permanent magnet in the rotor. In this case, the magnetic wedges are arranged at the slot openings of the stator core. In FIG. 13, the flat magnetic metal particles 10, the intervening phase 20, the magnetic wedges 100, the rotating electric machine 200, the rotor 210, the stator core 222, the excitation coil 232, the armature coil 234, the gap surface 240, and the core teeth 250 are shown.
[0077] Since a linear motor is a flat plate-shaped structure developed from a radial gap motor, the magnetic wedge of the present invention can be applied to the linear motor. That is, the stator may include a stator core and a field coil inserted into the slot of the stator core, and a magnetic wedge may be provided at the slot opening. FIG. 14 is a schematic diagram showing an example of a linear motor of this embodiment. In a linear motor, the moving direction of the mover, the direction perpendicular to the moving direction of the mover, and the direction perpendicular to the stator correspond to the rotation direction, axial direction, and radial direction of the radial gap motor, respectively. By disposing the magnetic wedge of this embodiment, it is possible to reduce harmonic loss generated on the surface of the mover while suppressing an increase in leakage flux. In addition, the magnetic flux passing through the gap increases, and thus the thrust of the linear motor is improved. As a result, high efficiency can be achieved. In FIG. 14, flat magnetic metal particles 10, intervening phases 20, magnetic wedges 100, a stator 220, a coil 230, a gap surface 240, iron core teeth 250, and a mover 290 are shown.
[0078] As described above, according to the rotating electric machine of this embodiment, the increase in leakage magnetic flux due to the use of magnetic wedges can be suppressed, and the pulsation of the magnetic flux distribution on the surface of the iron core can be effectively alleviated, thereby realizing high efficiency. Note that the slot shape of the rotating electric machine of this embodiment may be a semi-closed slot, but is preferably an open slot. In this case, harmonic loss can be significantly reduced, which is preferable.
[0079] The rotating electric machine of the present embodiment can be applied to transportation systems such as railways, electric vehicles, and hybrid cars, social systems such as elevators and air conditioners, industrial systems such as robots, pumps, compressors, and blowers, energy systems such as thermal power generators, hydroelectric generators, wind power generators, nuclear power generators, and geothermal generators, and home appliances such as washing machines, and can improve the efficiency of the system. In particular, in large-capacity industrial machines, an open slot is generally adopted as the slot shape, so it is preferable to include the magnetic wedge of the first embodiment. In addition, in main motors for railways, a form-wound coil is used because of the need to withstand high voltage and vibration, and an open slot is adopted as the slot shape, so it is preferable to include the magnetic wedge of the first embodiment.
[0080] In railways, the loss of rotating electric machines accounts for about half of the power consumption when the train is running, so the effect of improving efficiency by reducing the loss of rotating electric machines is large. Also, in electric vehicles and hybrid cars, the efficiency of the main motor can be improved by using the magnetic wedge of the first embodiment, so the driving range can be extended.
[0081] The present invention is expected to be effective for hydroelectric generators, particularly variable speed pumped storage generators, and also for wind power generators.
[0082] (Example) Examples 1 to 4 will be described in more detail below in comparison with Comparative Examples 1 and 2.
[0083] Example 1 First, a ribbon of Fe-Co-Si-B (Fe70Co30B25 (at%)-4wt%Si) is prepared using a single roll quenching device. The ribbon obtained is then heat-treated at 300°C in an H2 atmosphere. The ribbon is then pulverized using a mixer device to obtain flat magnetic metal particles (the average thickness is about 15μm, and the average ratio of the average length in the flat plane to the thickness is about 30). The flat magnetic metal particles obtained are then mixed with a bismaleimide resin and molded. In the molding, when applying a press pressure in one axial direction, a magnetic field is applied in a direction parallel to the direction of application of the press pressure. Then, hot press molding is performed. In the hot press molding, the hot press temperature and time are adjusted and stopped before hardening. Then, heat treatment is performed while applying a magnetic field in a direction parallel to the direction of application of the press pressure, and the magnetic wedge is completely hardened to produce a magnetic wedge. In addition, by adjusting the hot pressing temperature and time, the proportion of flat magnetic metal surface particles in which 10% or more of the length of the flat magnetic metal particles are positioned outside the average contour line in the width direction of the magnetic wedge to the total number of flat magnetic metal surface particles was adjusted, which was 1% in this Example 1.
[0084] Example 2 This is almost the same as Example 1, except that by adjusting the hot pressing temperature and time, the ratio of flat magnetic metal surface particles in which 10% or more of the length of the flat magnetic metal particles are positioned outside the average contour line in the width direction of the magnetic wedge to the total number of flat magnetic metal surface particles is set to 20%.
[0085] Example 3 This is almost the same as Example 1, except that by adjusting the hot pressing temperature and time, the ratio of flat magnetic metal surface particles in which 10% or more of the length of the flat magnetic metal particles are positioned outside the average contour line in the width direction of the magnetic wedge to the total number of flat magnetic metal surface particles is set to 50%.
[0086] Example 4 This is almost the same as Example 1, except that by adjusting the hot pressing temperature and time, the proportion of flat magnetic metal surface particles in which 10% or more of the length of the flat magnetic metal particles are positioned outside the average contour line in the width direction of the magnetic wedge to the total number of flat magnetic metal surface particles is set to 90%.
[0087] Comparative Example 1 The procedure is almost the same as in Example 1, except that the material is completely hardened by hot press molding, and then heat-treated while applying a magnetic field in a direction perpendicular to the direction of the applied pressure. At this time, there were no flat magnetic metal surface particles with 10% or more of their length located outside the average contour line in the width direction of the magnetic wedge.
[0088] Comparative Example 2 This is almost the same as Example 1, except that by adjusting the hot pressing temperature and time, the proportion of flat magnetic metal surface particles in which 10% or more of the length of the flat magnetic metal particles are positioned outside the average contour line in the width direction of the magnetic wedge to the total number of flat magnetic metal surface particles is 95%.
[0089] Table 1 shows the ratio of flat magnetic metal surface particles in which 10% or more of the length of the magnetic wedge of this embodiment is positioned outside the average contour line in the width direction of the magnetic wedge to the total number of flat magnetic metal surface particles, along with comparative examples 1 and 2.
[0090] Table 2 shows the magnetic permeability of the magnetic wedge of this embodiment, the degree of efficiency improvement as a rotating electric machine, the magnetic permeability after a heat resistance test, the degree of efficiency improvement as a rotating electric machine, the magnetic permeability after a heat resistance test of a sample after surface coating, the degree of efficiency improvement as a rotating electric machine, and strength, along with comparative examples 1 and 2.
[0091] (1) Magnetic permeability: The magnetic permeability is measured at 100 Hz in the middle between the width direction and the thickness direction of the magnetic wedge. The magnetic permeability is shown as a ratio based on the magnetic permeability of Comparative Example 1.
[0092] (2) Efficiency improvement as a rotating electrical machine: Using a standard radial gap type motor as a motif, the efficiency improvement is calculated based on the efficiency when a non-magnetic wedge is used. The efficiency improvement is shown as a ratio based on the efficiency improvement in Comparative Example 1.
[0093] (3) Permeability after heat resistance test: The permeability after heating in air at 250°C for 1000 hours (heat resistance test) (permeability at 100 Hz in the direction midway between the width direction and thickness direction of the magnetic wedge) was measured, and shown as a ratio to the permeability of the sample of Comparative Example 1 after heating in air at 250°C for 1000 hours (=permeability of evaluation sample after heating in air at 250°C for 1000 hours / permeability of Comparative Example 1 after heating in air at 250°C for 1000 hours).
[0094] (4) Efficiency improvement after heat resistance test: The efficiency improvement after heating in air at 250°C for 1000 hours (heat resistance test) is calculated. The efficiency improvement is shown as a ratio based on the efficiency improvement in Comparative Example 1.
[0095] (5) Permeability after heat resistance test of surface-coated sample: For the evaluation sample, a surface coating layer was formed using a bismaleimide resin, and the evaluation sample was heated in air at 250°C for 1000 hours (heat resistance test) to measure the permeability (permeability at 100 Hz in the direction midway between the width and thickness directions of the magnetic wedge). This is shown as a ratio to the permeability of the sample of Comparative Example 1 after heating in air at 250°C for 1000 hours (=permeability of evaluation sample after heating in air at 250°C for 1000 hours / permeability of Comparative Example 1 after heating in air at 250°C for 1000 hours).
[0096] (6) Degree of efficiency improvement after heat resistance test for surface-coated sample: A surface coating layer made of bismaleimide resin is formed on the evaluation sample, and the efficiency improvement is calculated after heating in air at 250°C for 1000 hours (heat resistance test). The degree of efficiency improvement is shown as a ratio based on the efficiency improvement in Comparative Example 1.
[0097] (7) Strength of surface-coated sample after heat resistance test: For an evaluation sample, a surface coating layer made of a bismaleimide resin was formed, and the evaluation sample was heated in air at 250°C for 1000 hours (heat resistance test), after which the flexural strength was measured at 25°C, and shown as a ratio to the flexural strength of the sample of Comparative Example 1 at 25°C after heating in air at 250°C for 1000 hours (= flexural strength of evaluation sample at 25°C after heating in air at 250°C for 1000 hours / flexural strength of Comparative Example 1 at 25°C after heating in air at 250°C for 1000 hours).
[0098] [Table 1]
[0099] [Table 2]
[0100] From Table 2, it can be seen that, compared to Comparative Examples 1 and 2, Examples 1 to 4 have excellent properties in terms of permeability, degree of efficiency improvement as a rotating electric machine, permeability after heat resistance test, degree of efficiency improvement as a rotating electric machine, permeability after heat resistance test of the sample after surface coating, degree of efficiency improvement as a rotating electric machine, and strength. This is thought to be because the flat magnetic metal surface particles in the magnetic wedge, the length of which is 10% or more of which is arranged outside the contour average line in the width direction of the magnetic wedge, are included in the total number of flat magnetic metal surface particles from 1% to 90%, and thus the magnetic flux can be efficiently guided in the rotating electric machine (permeability and efficiency are improved). In addition, it was found that such a structure allows the surface coating layer made of resin to be formed firmly, and thus the strength, permeability, and efficiency as a rotating electric machine after the heat resistance test can be maintained without deteriorating. On the other hand, in Comparative Examples 1 and 2, the flat magnetic metal surface particles in which 10% or more of the length of the flat magnetic metal particles are arranged outside the average contour line in the width direction of the magnetic wedge were 0% and 95% of the total number of flat magnetic metal surface particles, and the ease of guiding magnetic flux was poor, and the degree of improvement in magnetic permeability and efficiency was lower than in Examples 1 to 4. In Comparative Examples 1 to 2, the magnetic permeability after the heat resistance test and the degree of improvement in efficiency as a rotating electric machine were also lower than in Examples 1 to 4. Furthermore, in Comparative Examples 1 to 2, the surface coating layer made of resin was not formed firmly, and therefore the strength after the heat resistance test, the magnetic permeability, and the efficiency as a rotating electric machine were deteriorated, and it was found that the characteristics were lower than those of Examples 1 to 4.
[0101] Although some embodiments and examples of the present invention have been described, these embodiments and examples are presented as examples and are not intended to limit the scope of the invention. These novel embodiments can be implemented in various other forms, and various omissions, substitutions, and modifications can be made without departing from the spirit of the invention. These embodiments and their modifications are included in the scope and spirit of the invention, and are included in the scope of the invention and its equivalents described in the claims.
[0102] The above-described embodiment can be summarized as the following technical proposal. (Technical proposal 1) A magnetic wedge for a rotating electric machine, the magnetic wedge comprising a plurality of flat magnetic metal particles and an intervening phase; In a cross section perpendicular to the longitudinal direction of the magnetic wedge and at the center of the longitudinal direction, A magnetic wedge including flat magnetic metal surface particles, among the plurality of flat magnetic metal particles, where 10% or more of the length of the flat magnetic metal particles is positioned outside the average contour line in the width direction of the magnetic wedge. (Technical proposal 2) A magnetic wedge as described in Technical Proposal 1, in which, in a cross section perpendicular to the longitudinal direction of the magnetic wedge and at the center of the longitudinal direction, the flat magnetic metal surface particles, of which 10% or more of the length is positioned outside the average contour line of the width direction of the magnetic wedge, account for 1% or more and 90% or less of the total number of the flat magnetic metal surface particles. (Technical proposal 3) A magnetic wedge as described in Technical Proposal 1 or Technical Proposal 2, wherein in a cross section perpendicular to the longitudinal direction of the magnetic wedge and at the center of the longitudinal direction, the orientation angle of the flat magnetic metal surface particles, which are arranged outside the widthwise contour average line of the magnetic wedge for more than 10% of their length, is greater than or equal to 1 degree and less than 60 degrees with respect to the widthwise contour average line. (Technical proposal 4) A magnetic wedge according to any one of Technical Schemes 1 to 3, wherein the surface roughness Ra of a widthwise contour line in a cross section perpendicular to the longitudinal direction of the magnetic wedge and at the center of the longitudinal direction is 0.1 μm or more and 100 μm or less. (Technical proposal 5) A magnetic wedge according to any one of technical proposals 1 to 4, wherein at least a portion of the surface of the magnetic wedge is covered with a surface coating layer. (Technical proposal 6) A magnetic wedge as described in technical proposal 5, wherein the thickness of the surface coating layer is greater than or equal to the average thickness of the flat magnetic metal particles. (Technical proposal 7) A magnetic wedge described in any one of Technical Proposals 1 to 6, wherein the intervening phase is present between the multiple flat magnetic metal particles and contains at least one second element selected from the group consisting of oxygen (O), carbon (C), nitrogen (N) and fluorine (F). (Technical proposal 8) A magnetic wedge according to any one of technical proposals 1 to 7, wherein the intervening phase contains a resin. (Technical proposal 9) A magnetic wedge according to any one of Technical Schemes 1 to 8, wherein the intervening phase contains at least one resin selected from the group consisting of bismaleimide-based resins, polyimide-based resins, polyester-based resins, phenol-based resins, epoxy-based resins, and silicone-based resins. (Technical proposal 10) A magnetic wedge according to any one of technical proposals 5 to 9, wherein the surface coating layer contains a resin. (Technical proposal 11) A magnetic wedge described in any one of Technical Proposals 5 to 10, wherein the surface coating layer is a resin whose weight increase rate after exposure to air at 120°C for 30 minutes and then to room temperature for one week is 1% or less. (Technical proposal 12) A magnetic wedge according to any one of Technical Schemes 5 to 11, wherein the surface coating layer has a water absorption rate of 1% or less as defined by ISO 62:1999 (JIS K7209:2000). (Technical proposal 13) A magnetic wedge according to any one of Technical Schemes 5 to 12, wherein the surface coating layer contains at least one resin selected from the group consisting of bismaleimide-based resins, polyimide-based resins, polyester-based resins, phenol-based resins, epoxy-based resins, and silicone-based resins. (Technical proposal 14) A magnetic wedge described in any one of Technical Proposals 1 to 13, wherein the plurality of flat magnetic metal particles have an average thickness of 10 nm or more and 100 μm or less, have a magnetic metal phase containing at least one first element selected from the group consisting of Fe, Co and Ni, and have an average ratio of the average length within the flat surface to the thickness of 5 or more and 10,000 or less. (Technical proposal 15) A magnetic wedge described in any one of Technical Proposals 1 to 14, wherein at least a portion of the surface of the flat magnetic metal particle is covered with a coating layer having a thickness of 0.1 nm or more and 1 μm or less and containing at least one second element selected from the group consisting of oxygen (O), carbon (C), nitrogen (N) and fluorine (F). (Technical proposal 16) A magnetic wedge described in any one of Technical Solutions 1 to 15, having a difference in coercive force depending on the direction within the flat surface of the flat magnetic metal particle. (Technical proposal 17) A magnetic wedge according to any one of technical proposals 1 to 16, having a difference in coercive force depending on the direction within a plane parallel to the flat surface. (Technical proposal 18) A rotating electric machine equipped with the magnetic wedge described in any one of technical proposals 1 to 17. [Explanation of symbols]
[0103] 6: flat surface 9: Covering layer 10: Flat magnetic metal particles 20: Intervening phase 100:Magnetic wedge 200: Rotating motor 210: Rotor 220: Stator 222: Stator core 230: Coil 232: Excitation coil 234:Armature coil 240 :Void surface 250: Iron core teeth 260: Core slot 270: Stator 280: Axis 290: Mover
Claims
1. A magnetic wedge for a rotating electric machine, the magnetic wedge comprising a plurality of flat magnetic metal particles and an intervening phase; In a cross section perpendicular to the longitudinal direction of the magnetic wedge and at the center of the longitudinal direction, A magnetic wedge including flat magnetic metal surface particles, among the plurality of flat magnetic metal particles, in which 10% or more of the length of the flat magnetic metal particles is positioned outside the average contour line of the magnetic wedge in the width direction.
2. A magnetic wedge as described in claim 1, wherein in a cross section perpendicular to the longitudinal direction of the magnetic wedge and at the center of the longitudinal direction, the flat magnetic metal surface particles having 10% or more of their length arranged outside the average contour line of the width direction of the magnetic wedge account for 1% or more and 90% or less of the total number of the flat magnetic metal surface particles.
3. A magnetic wedge as described in claim 1, wherein in a cross section perpendicular to the longitudinal direction of the magnetic wedge and at the center of the longitudinal direction, the orientation angle of the flat magnetic metal surface particles, which are arranged outside the widthwise contour average line of the magnetic wedge for more than 10% of their length, is 1 degree or more and 60 degrees or less with respect to the widthwise contour average line.
4. 2. The magnetic wedge according to claim 1, wherein a surface roughness Ra of a widthwise contour line in a cross section perpendicular to the longitudinal direction of the magnetic wedge and taken at the center of the longitudinal direction is 0.1 μm or more and 100 μm or less.
5. 2. The magnetic wedge according to claim 1, wherein at least a portion of the surface of the magnetic wedge is covered with a surface coating layer.
6. 6. The magnetic wedge according to claim 5, wherein the thickness of said surface coating layer is equal to or greater than the average thickness of said flat magnetic metal particles.
7. The magnetic wedge according to claim 1, wherein the intervening phase is present between the flat magnetic metal particles and contains at least one second element selected from the group consisting of oxygen (O), carbon (C), nitrogen (N) and fluorine (F).
8. The magnetic wedge of claim 1 , wherein the intervening phase comprises a resin.
9. 2. The magnetic wedge according to claim 1, wherein the intervening phase contains at least one resin selected from the group consisting of bismaleimide-based resins, polyimide-based resins, polyester-based resins, phenol-based resins, epoxy-based resins, and silicone-based resins.
10. 6. The magnetic wedge of claim 5, wherein said surface coating layer comprises a resin.
11. 6. A magnetic wedge according to claim 5, wherein the surface coating layer is made of a resin whose weight increase rate after exposure to the atmosphere at 120[deg.] C. for 30 minutes and then exposure to the atmosphere at room temperature for one week is 1% or less.
12. 6. The magnetic wedge according to claim 5, wherein the surface coating layer has a water absorption rate of 1% or less as defined by ISO 62:1999 (JIS K7209:2000).
13. 6. The magnetic wedge according to claim 5, wherein the surface coating layer contains at least one resin selected from the group consisting of bismaleimide resins, polyimide resins, polyester resins, phenol resins, epoxy resins, and silicone resins.
14. A magnetic wedge as described in claim 1, wherein the plurality of flat magnetic metal particles have an average thickness of 10 nm or more and 100 μm or less, have a magnetic metal phase containing at least one first element selected from the group consisting of Fe, Co and Ni, and have an average ratio of the average length within the flat surface to the thickness of 5 or more and 10,000 or less.
15. A magnetic wedge as described in claim 1, wherein at least a portion of the surface of the flat magnetic metal particle is covered with a coating layer having a thickness of 0.1 nm or more and 1 μm or less and containing at least one second element selected from the group consisting of oxygen (O), carbon (C), nitrogen (N) and fluorine (F).
16. 2. The magnetic wedge according to claim 1, wherein the flat magnetic metal particles have a difference in coercivity depending on the direction within the flat plane.
17. 2. The magnetic wedge according to claim 1, wherein the magnetic wedge has a difference in coercivity depending on a direction in a plane parallel to the flat surface.
18. A rotating electric machine comprising the magnetic wedge according to claim 1.
Citation Information
Patent Citations
Magnetic component and manufacturing method thereof
JP2020061530A
Magnetic material and rotary electric machine
JP2021048238A
Magnetic wedge manufacturing method, magnetic wedge, stator for rotating electrical machine, and rotating electrical machine
JP2022126604A
Electric motor
JP2022128816A
Magnetic wedge, rotating electrical machine, and method for manufacturing magnetic wedge
WO2021033567A1